International Criminal Law II: International Crimes - Sokanović , Lucija (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
After a short recollection of the notion of International criminal law the author considers various doctrinal definitions of international crimes. Although there is not necessarily consensus on a definite list of crimes under international law, it is widely accepted that it would certainly include genocide, crimes against humanity, war crimes and the crime of aggression. In analysing the differences between international crimes and national crimes, several arguments highlight their origins in international customary or conventional law. The crimes of genocide, crimes against humanity, war crimes and finally the crime of aggression are presented by their definitions from the Rome Statute, doctrinal clarification and the case law of ad hoc tribunals as well as the International Criminal Court. The discussion surrounding accusations and institutes of international criminal law often reflects a variety of expert opinion and different case laws. In this chapter, aimed at students, the author emphasises the importance of maintaining a balanced perspective on definitive determinations.Keywords: international crimes, genocide, crimes against humanity, war crimes, the crime of aggression